Prevalence and antibiotic resistance of pathogens isolated from neurosurgical patients with postoperative central nervous system infections in a tertiary hospital in North China - Yang, Fan; Chen, Jingnan; Zhao, Mengjie; Zhao, Hejun; Yang, Bin; Feng, Xuequan (Frontiers in Public Health, 2025)
BackgroundPostoperative central nervous system infection (PCNSI) is a serious complication following neurosurgery. Effective clinical management of PCNSI requires prompt antibiotic administration based on the identification of the causative pathogens and antibiotic resistance. This study aimed to investigate the causative pathogens of PCNSI and their antibiotic resistance profiles, which could help clinicians initiate appropriate empirical antibiotic therapy.MethodsThe distribution and antimicrobial resistance of pathogens in patients with PCNSI from January 2014 to December 2023 were analyzed retrospectively. Cerebrospinal fluid samples were aseptically collected and subjected to standard microbiological methods for bacterial isolation and identification. Antibiotic sensitivity testing was performed via the Kirby–Bauer disk diffusion agar method.ResultsA total of 396 patients were diagnosed with PCNSI, and 385 pathogens were identified from these patients. The percentages of Gram-positive bacteria, Gram-negative bacteria, and fungi were 56.10, 41.30, and 2.60%, respectively. The predominant pathogens among the Gram-positive bacteria were coagulase-negative staphylococci (29.09%), whereas Acinetobacter baumannii (14.29%) was the most common Gram-negative bacterium. Compared with those from 2014 to 2018, the proportions of Enterococcus and Acinetobacter baumannii increased markedly from 2019 to 2023. Antimicrobial susceptibility testing revealed that all Gram-positive bacteria had 100% sensitivity to vancomycin and linezolid, whereas imipenem, meropenem, and amikacin were most effective against Gram-negative bacteria.ConclusionGram-positive bacteria, especially coagulase-negative staphylococci, were the predominant pathogens causing PCNSI. Furthermore, several Gram-negative species, especially Klebsiella pneumoniae and Acinetobacter baumannii, showed concerning trends of increasing resistance to common antibiotics. Acinetobacter baumannii showed an increasing proportion of infections, posing a clinical challenge due to the limited number of effective antibiotics.